Slovo imeet Tatarstan . Slovo imeet Tatarstan . Tatarstan Speaking . Слово имеет Татарстан - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion with Farid Mukhametshin on political events in the Republic of Tatarstan. Featured in the program: Mukhametshin, Farid Khairullovich (Chairman of the Supreme Council of the Republic of Tatarstan) Интервью с Фаридом Мухаметшином о политических событиях в Республике Татарстан. В программе участвуют: Мухаметшин, Фарид Хайруллович (Председатель Верховного Совета Республики Татарстан)